Addressing child streetism in the La-Nkwantanang madina municiplaity - AMEKUEDI, Gifty Lebenam (KDI School, 2016)
In a fast growing world social problems are unavoidable as population and human activities increase. Child Streetism, one such problem is examined by this paper to investigate its manifestations in the La-Nkwantanang Municipality. The study falls on the systems theory to examine key systems in society that exist to ensure the effective running of the society and survival of all individuals. A snowballing sampling method is adopted for the study due to the sensitivity of the study. The study adopted the mixed method approach, combining qualitative and quantitative measures to interpret and discuss findings. Economic hardship was evaluated to have led most children to the street to work to support themselves and their families. There was also the realisation of a growing norm whereby children are expected to contribute to the economic sustenance of their families, thus, resulting in more and more parents sending their children to work in the streets seeing nothing wrong with it. Significantly, most children resort to streetism because of the economic activity they engage in. There is enough evident to conclude that the problem of child streetism in Madina and for that matter Ghana at large has seen very little intervention especially on the part of the state. It is recommended that the state of Ghana designs and adopt a national policy to be implemented at the District levels to deal with the problem of child streetism as no such state policy exists. Also, NGOs such as SAID and CAS should strengthen their capacities to effectively address child streetism. Finally, Child Streetism Departments should be set up at the local assemblies to sensitise and educate families and children on the mitigation of child streetism.
Thesis(Master) --KDI School:Master of Development Policy,2016